2018
DOI: 10.1016/j.bone.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of lean and fat mass to bone strength in young Hispanic and non-Hispanic girls

Abstract: Lean mass is the main determinant of bone strength for appendicular skeletal sites. Fat mass contributes to bone strength in the weight-bearing skeleton but does not add to bone strength in non-weight-bearing locations and may potentially be detrimental. Bone vBMD, geometry, and strength did not differ between Hispanic and non-Hispanic girls; fat mass may be a stronger contributor to bone strength in weight-bearing bones of Hispanic girls compared to non-Hispanic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
(66 reference statements)
0
15
1
1
Order By: Relevance
“…In a previously published analysis of cross‐sectional data from the STAR study, Hetherington‐Rauth and colleagues found that fat mass was positively associated with bone strength and size at the 66% tibia, bone size at the 20% femur and 4% tibia, and cortical thickness and BMC at the radius. ( 19 ) The present longitudinal analysis showed a positive relationship between change in TBFM and 66% tibia bone strength, after adjusting for TBLM, but change in TBFM did not significantly influence bone outcomes at the 20% femur nor 4% tibia after adjusting for TBLM. Additionally, our longitudinal analysis identified a significant relationship between change in TBFM on radius SSI p (dependent on menarcheal status) that was not observed in the cross‐sectional analysis.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In a previously published analysis of cross‐sectional data from the STAR study, Hetherington‐Rauth and colleagues found that fat mass was positively associated with bone strength and size at the 66% tibia, bone size at the 20% femur and 4% tibia, and cortical thickness and BMC at the radius. ( 19 ) The present longitudinal analysis showed a positive relationship between change in TBFM and 66% tibia bone strength, after adjusting for TBLM, but change in TBFM did not significantly influence bone outcomes at the 20% femur nor 4% tibia after adjusting for TBLM. Additionally, our longitudinal analysis identified a significant relationship between change in TBFM on radius SSI p (dependent on menarcheal status) that was not observed in the cross‐sectional analysis.…”
Section: Discussioncontrasting
confidence: 53%
“…Methodology for the cross‐sectional study has been previously reported. ( 19 ) For the longitudinal study, all measurements were taken at baseline and 2‐year follow‐up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of bone and body mass is more complex than generally assumed and "unlikely to be driven principally by the loading imparted by body mass due to gravity" (Pomeroy et al 2018). Although fat mass is a component of body mass and contributes to skeletal loading, lean mass is the main determinant of limb bone strength, particularly on upper limbs (Hetherington-Rauth et al 2018;Pomeroy et al 2018). Skeletal properties can be used to estimate lean mass but they are not reliable for estimating fat mass (Pomeroy et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high correlation, BMI is not an ideal predictor of %BF either in children and adolescents or in adults (Deurenberg-Yap et al 2000;Wells 2018;Wickramasinghe 2012). The relationship further depends on ethnicity as, for example, Asians have a lower BMI but at the same time a higher %BF (Deurenberg-Yap et al 2000;Prentice and Jebb 2001), however, bone measures do not differ significantly between ethnicities (Hetherington-Rauth et al 2018). Although "bone mass, skeletal muscle mass, and fat mass are highly correlated with BMI" (Wells 2014), BMI is only a measure of height and weight and not body composition.…”
Section: Figurementioning
confidence: 99%